EFEKTIFITAS SENAM KAKI TERHADAP NILAI ANKLE BRACHIAL INDEX PADA PENDERITA DIABETES MELLITUS TIPE 2: The Effectiveness of Foot Gymnastics on the Value of Ankle Brachial Index in Type 2 Diabetes Mellitus Patients - Made Mahaguna Putra; Ida Ayu Mas Narayani; I Komang Gde Trisna Purwantara; NI Made Dwi Yunica Astriani (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2020)
Introduction: One complication of DM is a blood circulation disorder. Ways that can be done to prevent symptoms of complications are non-pharmacological therapy of foot gymnastics. Foot gymnastics is a physical exercise activity that prevents complications and is effective in increasing blood circulation. Method: The research method used the pre-experimental design approach with the design of the one group pretest-posttest design. The sample consisted of 54 respondents. The sampling technique used is nonprobability sampling, namely purposive sampling, collecting data using observation sheets measuring the value of ABI. Results: The results of the Paired T-Test statistical test obtained a value of p = 0.001, which means that there is an effect of Foot Gymnastics Against the Value of Ankle Brachial Index in Patients with Type 2 DM in the Work Area of ??Banjar II Health Center. Discussion: From the results of the study, it was found that the more age increases the risk of developing circulatory disorders. Where respondents with advanced age are in the category of moderate vascular disease.